Functional specialization in regulation and quality control in thermal adaptive evolution. (15th September 2015) - Yama, Kazuma; Matsumoto, Yuki; Murakami, Yoshie; Seno, Shigeto; Matsuda, Hideo; Gotoh, Kazuyoshi; Motooka, Daisuke; Nakamura, Shota; Ying, Bei‐Wen; Yomo, Tetsuya
Abstract : Distinctive survival strategies, specialized in regulation and in quality control, were observed in thermal adaptive evolution with a laboratory Escherichia coli strain. The two specialists carried a single mutation either within rpoH or upstream of groESL, which led to the activated global regulation by sigma factor 32 or an increased amount of GroEL/ES chaperonins, respectively. Although both specialists succeeded in thermal adaptation, the common winner of the evolution was the specialist in quality control, that is, the strategy of chaperonin‐mediated protein folding. To understand this evolutionary consequence, multilevel analyses of cellular status, for example, transcriptome, protein and growth fitness, were carried out. The specialist in quality control showed less change in transcriptional reorganization responding to temperature increase, which was consistent with the finding of that the two specialists showed the biased expression of molecular chaperones. Such repressed changes in gene expression seemed to be advantageous for long‐term sustainability because a specific increase in chaperonins not only facilitated the folding of essential gene products but also saved cost in gene expression compared with the overall transcriptional increase induced by rpoH regulation. Functional specialization offered two strategies for successful thermal adaptation, whereas the evolutionary advantageous was more at the points of cost‐saving in gene expression and the essentiality in protein folding. Abstract : Two highly comparable molecular mechanisms, rpoH‐initiated gene regulation and chaperonin‐initiated quality control, were selected by E. coli for survival during thermal adaptive evolution. Multilevel analyses revealed the thermal adaptive evolution favored fewer and localised changes in gene expression and protein folding. The results indicated a cost‐saving strategy in both gene expression regulation and protein quality control, which may contribute to the overall homeostatic framework of cellular physiology.